Assessment of farmers perception to corporate institutional for the development of sheep farming in the village : Case study in the villages of Jambu sub district, district of Semarang - Pranadji, Tri; Sudaryanto, B (Indonesian Animal Sciences Society, 1999)
The objective of the study is to determine that sheep farming in the villages to increase farmers welfare could be developed taken into consideration of farmers perception and attitude which were included in the planning of development programme. In order to achieve the objective more effectively, the institutional system of sheep farming needs to be transformed into a corporate institution. Field study was conducted during the period of 1994-1997 in two villages of Jambu sub district, District of Semarang. Two approaches were used simultaneously, i.e. ideografis and nomotetis to analyze the data and information. Result s showed that, first, sheep farming in the villages still had big development opportunity .second, the threat of stagnation in the sheep farming may occur due to high dependency on family labor and lack of capital. Third, due to top down policy and lack of vision on the agrobusiness activities, the development of sheep farming could be hampered. Fourth, transforming into a corporate institution may increase economic profitability of sheep farming as well as performance of the farms. Fifth, in order to realize the development of corporate business systems, need to establish a pilot project. To implement the concept, support from banking institution especially for discount rate was necessary, along with the involvement of ATAI (Agricultural Technology Assessment Institutes), local livestock services, credit system and local government leader that has people oriented vision.